Application Of The Contextual Teaching And Learning Model In Mathematics Learning SPLDV Material - Adinda Aprillia Makaluas; Philotheus E. A. Tuerah; Vivian Regar (Simpati, 2023)
The purpose of this study is to compare the learning outcomes of students who were taught a system of linear equations with two variables using the Contextual Teaching and Learning model versus those who were taught the same material using the Direct Instruction methodology. Class VIII-1, which used the Contextual Teaching and Learning approach, and class VIII-2, which used the Direct Instruction model, were the topics. This study used a Posttest Only Control Group Design and a Quasi-Experimental Method. The sample for this study was drawn from two classes, specifically classes VIII1 and VIII2, each of which included 25 pupils. Both classes were equal and uniform. This data analysis is tested using the t-test with the parameters tcount = 5.020 > ttable = 2.059. H1 is accepted because H0 is refused. For instance, the Contextual Teaching and Learning (CTL) methodology can help students learn more effectively utilizing social math tools.